Miniatury Kodeksu Behema jako ilustracja warunków pracy i mieszkania mieszczan (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
THE MINIATURES FROM BEHEM’S CODE — AN ILLUSTRATION OF WORK AND LIVING CONDITIONS OF BURGHERSIn 1505 Baltazar Behem, a town clerk, donated a code including guild charters, laws and statutes decorated with 27 miniatures to the Cracow City Council. Most of them represent craftsmen at work; part of them represent guild emblems with items manufactured by the guild members or the symbols of their work. The miniatures show manufacturing skills along with the tools used and the products manufactured. They also show craftsmen’s workshop furnishing — all kinds of tables, benches, chests, cabinets, lavabos, stools etc. Some miniatures represent interiors that may be regarded as living rooms rather than workshops. Several other miniatures depict townscape and its environs. Although the items and the interiors shown in the miniatures are modelled after the German prints, they are generally realistic. However, the townscape and the town environs modelled after Flemish painting and prints do not in the least portray the Cracow of the beginning of the 16th century.